A Suggested Algorithm for Video Motion and Applicate It to Basketball - Basil Thanoon; Abeer Thanoon (Al-Rafidain Journal of Computer Sciences and Mathematics)
In this research, we study video motion for movable object within video sequence, and the target is a ball, where video and image processing are combined together. The video files that we have here the Audio Video Interleaves (AVI) type. Here, the video frames have been are read from video file directly, then each frame is processed without the need of frames conversion into separate images. This research includes algorithm suggestion to estimate ball position in each video frame then plotting the ball motion track along the video sequence, by choosing ball initial position and creating ball-rounding window and applying the adaptable threshold to the produced window in order to obtain binary representation window. Recreational process for colors has been made to be used in the following video frame processing, than to find the center of the gravity of the ball for obtaining the predicted object position in the following frame. ActiveX Control is used to display video sequence inside MATLAB6.5 language thorough using Graphical User Interface. Also Root Mean Square Error is adopted as a measure for the adjacent position to the real position of the ball within the video sequence and the position that is found by using algorithm. The experimental results show the efficiency of the suggested algorithm to estimate the ball position accurately.